Effect of maternal cold exposure on brown adipose tissue and thermogenesis in the neonatal lamb. - Symonds, M E (1992)
1. This study examines the effect of chronic cold exposure during pregnancy, induced by winter shearing twin-bearing ewes 4 weeks before predicted lambing date, on O2 consumption and CO2 production during non-rapid-eye-movement (REM) sleep in lambs maintained for at least 1 h at warm (28-18 degrees C) and cold (14-5 degrees C) ambient temperatures at 1, 4, 14 and 30 days of age. This was combined with measurement of the thermogenic activity (GDP binding to uncoupling protein in mitochondrial preparations) of perirenal adipose tissue from lambs immediately after birth and at 33 days of age. 2. Lambs born from shorn (cold-exposed) ewes were 15% heavier (P < 0.01) and possessed 21% (P < 0.01) more perirenal adipose tissue that contained 40% more protein and mitochondrial protein than unshorn (P < 0.05) controls. Total GDP binding in perirenal adipose tissue was 40% greater (P < 0.05) in lambs born from shorn ewes but there was no difference in lipid content of this tissue between the two groups. 3. At 1 day of age, lambs born from shorn ewes exhibited a 16% higher (P < 0.05) rate of O2 consumption (per kilogram bodyweight) at the warm temperature and a 40% greater metabolic response to the cold ambient temperature. All lambs born from shorn ewes responded to cold exposure without shivering (i.e. via non-shivering thermogenesis) whilst shivering was measured in four out of seven lambs in the unshorn group. These differences had disappeared by 4 days of age as a result of a 25% increased (P < 0.01) rate of O2 consumption in the warm in lambs born from unshorn ewes and a 20% decrease (P < 0.05) in the response to the cold in lambs from shorn ewes. Shivering during cold exposure was measured in six out of nine lambs born from shorn ewes indicating a rapid alteration in thermoregulatory responses to cold during the first few days of life. 4. The levels of GDP binding and mitochondrial protein in perirenal adipose tissue fell by one-third in both groups of lambs during the first 33 days of life whereas lipid content either increased or was unchanged. This indicated that brown adipose tissue (BAT) was developing the characteristics of white adipose tissue.(ABSTRACT TRUNCATED AT 400 WORDS)